Avaliação Node-Place do sistema de transporte público metroviário da cidade de São Paulo - Rodrigues, Thiago Teiji Sato Velasco (Universidade Federal de São Carlos, 2026)
The metro system of São Paulo city is considered essential for urban mobility in the São Paulo metropolitan area and, given the daily volume of riders, the relationship between the system's access points and the urban space where it is inserted becomes an important element for urban planning and a driver of public policies. This study applies the Node-Place methodology, with adaptations, to evaluate the metro stations of São Paulo's urban rail system according to their connectivity with the public transport network, their functionality within the urban space, and their accessibility via different active transport modes. The results were also analyzed in relation to the sociodemographic profile of the population surrounding the areas of each station. The research is structured based on a bibliographic and bibliometric review that identifies the main indicators used in similar studies, which are organized into three categories: Node (connectivity), Place (land use), and Active Mobility (accessibility via active modes). An adaptation of the Analytic Hierarchy Process (AHP) was applied to weight the indicators based on their frequency in the literature and to calculate final scores for each category. Data were collected from official sources and analyzed using geoprocessing techniques, allowing for the analysis of all stations in the city’s metro network. Preliminary results reveal spatial inequalities among the stations, with higher performance in those located in central areas of the city, such as Sé, República, and Anhangabaú stations, which showed a high level of connectivity, diverse land use, and favorable conditions for active mobility, alongside a concentration of high-income and working age population. On the other hand, stations located at the edges of the network, such as Capão Redondo, Vila Sônia, and Campo Limpo, performed lower and presented a surrounding population more dependent on the quality of public transport infrastructure, including children, elderly and women, highlighting challenges in urban integration and the redevelopment potential of these areas. The methodology applied to the São Paulo context enables the identification of opportunities for intervention and territorial improvement, contributing to the strengthening of the public transport system and to more equitable, efficient urban planning aligned with the principles of Transit-Oriented Development (TOD).
Node-Place analysis of the metro public transportation system in São Paulo city
Keywords: Transporte público; Node-Place; Mobilidade urbana; Geoprocessamento; São Paulo; ENGENHARIAS::ENGENHARIA CIVIL::INFRA-ESTRUTURA DE TRANSPORTES; 11. Cidades e Comunidades Sustentáveis